Towards the implementation of energy harvesting for IoT sensor nodes in an early warning flood detection system - Mohd Yazid, Mohd Aizat; Haja Mohideen, Ahmad Jazlan; Mohd Rodzi, Mohd Zuhaili; Husman, Muhammad Afif; Afif, Abdul Rahman; Mohd Zaki, Hasan Firdaus; Kumar, Deepak (Engineering and Technology Publishing, 2020)
Flood sensors are deployed to measure the water level of rivers in areas prone to flooding. Flood is a frequent event in many places and the after effect almost always results in loss of properties and lives. Deploying sensors in remote areas to provide significant benefit in mitigating the after-effects of flood, however, it is not simple as the nodes would require a constant source of clean energy. This research explores the potentials of energy harvesting as a means for the sensor nodes to be self-sustaining by using a clean source of energy in order to achieve constant monitoring of water levels in remote flood-prone areas.